Hubungan Pengetahuan, Motivasi Dan Dukungan Keluarga Dengan Pelaksanaan Metode Kangguru Di RSUD Cimacan : The Relationship Between Knowledge, Motivation, and Family Support with the Implementation of the Kangaroo Method at Cimacan Regional Hospital - Yuliyanti (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: PMK is part of LBW babies. The purpose of this study was to determine the relationship between knowledge, motivation, and family support with the kangaroo care method at Cimacan Hospital in 2022. Every pregnant woman wants the child she gives birth to have sufficient birth weight because babies with low birth weight (LBW) in addition to requiring more complicated and intensive care also increase infant morbidity and mortality. The purpose of this study was to determine the relationship between knowledge, motivation, and support. Families with the Implementation of Kangaroo Method Treatment at Cimacan Regional Hospital in 2022. Methods: This type of research uses quantitative analysis with a cross-sectional approach. The sample in the study used total sampling. The subjects in this study were mothers who had LBW babies who were treated at Cimacan Hospital in December 2022. This research was carried out in the Perinatology Room of Cimacan Hospital on December 1-12 2022. Results: The results of this study are most of them have a good understanding 39 (78%) most of the respondents are well motivated as many as 36 (72%), and most of the families are supportive 45 (90%) from the results of the chi-square test, the p-value < 0,05 means that there is a relationship between knowledge, motivation, and family support for KMC. Discussion: Then there is a relationship between knowledge, motivation, and family support with KMC.